2016
DOI: 10.1007/s11274-016-2159-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and purification of galacto-oligosaccharides: state of the art

Abstract: Lactose-derived non-digestible oligosaccharides are prominent components of functional foods. Among them, galacto-oligosaccharides (GOS) outstand for being prebiotics whose health-promoting effects are supported on strong scientific evidences, having unique properties as substitutes of human milk oligosaccharides in formulas for newborns and infants. GOS are currently produced enzymatically in a kinetically-controlled reaction of lactose transgalactosylation catalyzed by β-galactosidases from different microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 146 publications
0
60
0
7
Order By: Relevance
“…In addition, some galactosidases also function as a transgalactosidase enzyme, conjugating the liberated galactose residues back to a glycan or oligosaccharide terminus. [26] Lectins avoid confounding results that may be obtained using enzymes with different properties and from different sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some galactosidases also function as a transgalactosidase enzyme, conjugating the liberated galactose residues back to a glycan or oligosaccharide terminus. [26] Lectins avoid confounding results that may be obtained using enzymes with different properties and from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of some galactosidase enzymes to simultaneously function as a transgalactosidase as well as an exoglycosidase must also be considered. [26] Additionally, the specificity, catalytic rate, and conditions required for the enzyme reaction must be defined. [27] To expand research in glycan characterization, analytical technologies are required that are inexpensive, simple to implement and have potential for automated analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with the genuine progress of biotechnology whey is becoming a substrate of choice for diverse food and pharmaceutical industries (Kareb & A€ ıder, 2018;Lata et al, 2018). With the increased interest in functional foods and prebiotics, one of the promising approaches for whey valorization through conversion of present lactose by virtue of transgalactosylation activity of b-galactosidase (Torres et al, 2010;Vera et al, 2016;Panesar et al, 2018). Namely, wide range of physiologically active compounds collectively named galacto-oligosaccharides (GOS) could be produced by b-galactosidase mediated transfer of galactosyl moiety onto other saccharide molecules, resulting in the formation of a complex mixture of carbohydrates notably varying in polymerization degree, type of linkages, and their properties (Gosling et al, 2010;Carevi c et al, 2016a;Chen & G€ anzle, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After more than four decades of development, enzyme immobilization is still facing many challenges with ample room for future opportunities in different fields of applications. Some industrial examples of the use of immobilized enzymes are found in the fields of sweeteners (DiCosimo, McAuliffe, Poulose, & Bohlmann, 2013), interesterification of edible oils and fats (Macrae & Hammond, 1985;Samoylova, Sorokina, & Parmon, 2016), prebiotics (Vera et al, 2016), and antibiotics (Illanes & Valencia, 2017). From all the advantages associated to immobilized enzymes as process catalysts, two are particularly relevant to their application in winemaking, namely, the production of a catalyst-free product and the development of a continuous process (Bolivar, Eisl, & Nidetzky, 2016;Poppe, Fernandez-Lafuente, Rodrigues, & Ayub, 2015).…”
Section: Introductionmentioning
confidence: 99%